2019
DOI: 10.1161/circoutcomes.118.004741
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Future Cardiovascular Events in Patients With Peripheral Artery Disease Using Electronic Health Record Data

Abstract: Background: Patients with peripheral artery disease (PAD) are at risk of major adverse cardiac and cerebrovascular events (MACCE). There are no readily available risk scores that can accurately identify which patients are most likely to sustain an event, making it difficult to identify those who might benefit from more aggressive intervention. Thus, we aimed to develop a novel predictive model -using machine learning methods on electronic health record (EHR) data -to identify which PAD patients are most likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…Regarding CV risk stratification, Ross EG et al reported that state of the art ML algorithms outperformed stepwise logistic regression models for the identification of PAD and the prognostication of mortality risk in this population [ 144 ]. More recently, they have demonstrated that the application of ML to electronic health records can generate learning-based models that accurately identify PAD patients at risk of future major adverse cardiac and cerebrovascular events [ 145 ]. In addition, ML algorithms might be useful to predict not only PAD medical burden, but also its associated financial cost.…”
Section: Machine Learning and Padmentioning
confidence: 99%
“…Regarding CV risk stratification, Ross EG et al reported that state of the art ML algorithms outperformed stepwise logistic regression models for the identification of PAD and the prognostication of mortality risk in this population [ 144 ]. More recently, they have demonstrated that the application of ML to electronic health records can generate learning-based models that accurately identify PAD patients at risk of future major adverse cardiac and cerebrovascular events [ 145 ]. In addition, ML algorithms might be useful to predict not only PAD medical burden, but also its associated financial cost.…”
Section: Machine Learning and Padmentioning
confidence: 99%
“…The second set contained 30% (475 samples) from both classes SARS-CoV-2 (189 samples) and non-SARS-CoV- 2 (286 samples) and was used as a testing dataset with the trained model. The classifiers were validated via ten-fold CV, and the best model was selected based on the F-measure [ 43 ], which balances the recall and precision of the model. In addition, the efficacy of the model was evaluated on the accuracy matrix via the corrected 10x10 fold CV paired t-test [ 44 ].…”
Section: Machine Learning Classifiersmentioning
confidence: 99%
“…In contrast, unsupervised machine learning leaves the algorithms to discover on their own the underlying structure within unlabeled data. The machine learning based algorithms with strong data processing ability have become a promising methodology for clinical decision making and medicine study, including clinical prediction, radiology, surgery, drug discovery and pharmacokinetic prediction [1315]. In the field of reproduction science, machine learning has been applied in areas including embryo scoring and prediction of implantation rate after blastocyte transfer [16, 17].…”
Section: Introductionmentioning
confidence: 99%